PELATIHAN PEMBUATAN KAMUS BAHASA INDONESIA DI SDN VI SIMOKERTO SURABAYA - Nensy Megawati Simanjuntak; Wahyu Widayati; Arusmtyas Puspitaning P (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
The partner of this community service activity is SDN Simokerto VI/139 which is located at Jalan Sidotopo Wetan No. 112 Surabaya Based on the teacher's observations and interviews with school principals, one way to develop the teaching profession by writing scientific papers is to make a dictionary. The dictionary is a collection of meaningful words, very important for teachers as a means of writing and as a medium of learning while students can find out the meaning of various vocabulary words. . The partner's problem is that in the Library of SDN Simokerto VI, there are no general dictionaries or dictionaries for elementary schools that students can use to develop vocabulary or look for meaning in learning. This PPM activity aims to equip SDN Simokerto VI teachers to be able to compile and utilize dictionaries. for elementary schools. The training participants were teachers at SDN Simokerto VI and librarians, as well as school principals. The results of PPM activities were that all participants understood dictionaries, could compile dictionaries, and could use dictionaries for elementary schools.